Energy loss analysis of a large scale BIPV system for university buildings in tropical weather conditions: a partial and cumulative performance ratio approach - Kumar, Nallapaneni Manoj; Mahendran, Samykano; Karthick, A. (Elsevier, 2021)
This paper evaluates and discusses the building-integrated photovoltaic (BIPV) system energy losses during the energy conversion process from sunlight into electricity. An approach based on partial performance ratio (P-PR) and cumulative performance ratio (C-PR) is used. The P-PR and C-PR are evaluated considering eight stages possible in the energy conversion stage in photovoltaic (PV) energy systems. A large-scale BIPV system is proposed by retrofitting the existing university buildings is investigated, and the observed results depict the impact of energy losses over the performance ratio decline. Results showed that the P-PR of the BIPV as per eight energy conversion stages varies between 85.6 and 100%. The C-PR varies between 74 and 100%, recording an overall system performance ratio (PR) of 74% under tropical weather conditions. The energy losses are varied within the range of −0.27 to −14.8% (−4 to −223 kWh/kWp) in different energy conversion stages. The total energy losses in the BIPV system account for 26% (−419 kWh/kWp). Based on the observations, reasons for various losses and their mitigation strategies are explored. Thus, we believe this study could provide useful information on the feasibility of considering retrofitting the university buildings with the BIPV modules.